Diet of Phyllodactyllus reissi (Sauria:Gekkonidae) in the Zona Reservada de Tumbes, Peru - Jordán, Juan C. (2006)
The purpose of this paper is to describe the diet of Phyllodactylus reissi, a nocturnal common gecko distributed from southern Ecuador to central Perú. A total of 15 individuals were captured inside buildings at Quebrada Faical, El Caucho and Bocana Murciélago in the Zona Reservada de Tumbes. Coleoptera and Blattoptera were the dominant preys from a total of six prey types found in stomachs. The number of prey per stomach were between 1 to 9, with 3 preys in average; the prey length average was 8,98 mm with a range of 1 to 25mm; the prey volume average was 61,97 mm3 with a range of 0,13 to 670,8 mm3 . The snout-vent length and snout length were not significantly related with average prey lengths and volumes. Phyllodactylus reissi has generalist habits with respect to diet and shows a tendency to consume medium-sized preys in the Zona Reservada de Tumbes.